Wildfire-Related Catastrophes: The Need for a Modern International Safety Investigation Procedure - Vuorio, Alpo; Kovanen, Petri T.; Budowle, Bruce; Sajantila, Antti; Palo, Jukka U.; Stoop, John (Frontiers in Climate, 2021)
Despite the increased frequency and scale of wildfire-related catastrophes, there has been little or no effective and coordinated international policy to address their highly negative impact. Possibly a generalised approach to respond to such major events could be modelled on existing international safety investigation policies and agreements that already have proved successful. The International Civil Aviation Organization (ICAO) outlines safety investigations after international fatal aviation accidents. Although this well-established safety investigation protocol cannot be directly applied in acute wildfire-related accidents, it can offer a useful framework for establishing international guidelines to reduce risk of future wildfire catastrophes. The co-operation between safety investigation authorities has been shown to be fruitful especially for those less developed countries that have limited resources and experience related to accident investigations. While primarily an adaptive measure that can set practices to reduce vulnerability and fragility of ecosystems and human societies, the same policies could be seen as a climate change mitigation measure, as wildfires can contribute significantly to global CO2 emissions. Finally, the concept of independent and qualified safety investigations represents the principle of serendipity: disclosing by accident something that has not been foreseen. Feedback from reality compensates assumptions and limitations of feedforward analysis of complex systems that can only reveal their dynamics and performance in reality and over time.